Grenzüberschreitungen / Traversées des frontières - Aude Therstappen (Recherches Germaniques)
Far from being a simple stylistic exercise, a literary journal must be understood as a positioning of research, a point of balance between the time of analysis, the time of writing and the time of presentation. The library collections are at once its foundation, roots and depth. The journal Recherches germaniques, with its ‘naturally’ comparative positioning, its dual focus on German literature and history of thought, and the place it reserves for Alsace, is thus intimately linked to the collections of the Bibliothèque nationale et universitaire de Strasbourg, formerly the Kaiserliche Universitäts- und Landesbibliothek. Destroyed and then reconstituted thanks to international donations and in particular those from the German Empire, the collections of the Bnu constitute a privileged mirror of the eventful history of the region. A source of inspiration for researchers, its collections are highlighted by the research published in the journal, which in turn guides the development of new bodies of authors as well as work to improve the identification of particular collections. This shared history has become the richness of a double culture, which is now used to open up research to the city.